Pls pls Pls pls Pls Pls help me pls pls pls pls pls pls ASAP pls pls pls Pls pls Pls pls Pls Pls help me pls pls pls pls pls pls ASAP pls pls pls I WILLLL GIVVVE BRAINLIEST!!!!!

Pls pls Pls pls Pls Pls help me pls pls pls pls pls pls ASAP pls pls pls Pls pls Pls pls Pls Pls help me pls pls pls pls pls pls ASAP pls pls pls I WILLLL GIVVV class=

Respuesta :

Answer:

x=9/2

Step-by-step explanation:

2(x−2)+10=6x−12

Step 1: Simplify both sides of the equation.

2(x−2)+10=6x−12

(2)(x)+(2)(−2)+10=6x+−12(Distribute)

2x+−4+10=6x+−12

(2x)+(−4+10)=6x−12(Combine Like Terms)

2x+6=6x−12

2x+6=6x−12

Step 2: Subtract 6x from both sides.

2x+6−6x=6x−12−6x

−4x+6=−12

Step 3: Subtract 6 from both sides.

−4x+6−6=−12−6

−4x=−18

Step 4: Divide both sides by -4.

−4x−4=−18−4

x=9/2

Hope this helps :)

Answer:

<=>2(x-2) -6(x-2) +10=0

<=>(x-2)(2-6)+10=0

<=>-4(x-2)=-10

=>x=9/2

ACCESS MORE